A COMPARATIVE EVALUATION OF MICROLEAKAGE, COMPRESSIVE STRENGTH, FLEXURAL STRENGTH AND FLUORIDE RELEASE OF ZIRCONOMER AND KETAC SILVER: AN IN VITRO STUDY. - VEMAGIRI, CHARANTEJA; Uloopi KS; Vinay Chandrappa; Anusha Ch (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: A successful restorative material forms a better adhesion, resist the microleakage and releases fluoride. However, existing glass ionomer cements cannot be used as a posterior restorative material in stress bearing areas. A new ionomer called Zirconomer, zirconia reinforced glass ionomer claims to exhibit high physical and biological properties. Aim: To assess and compare the microleakage, compressive strength, flexural strength and fluoride release from zirconomer with ketac silver. Materials & Methods: On twenty caries free premolar teeth (10 per each group), a class v cavity was restored with zirconomer and ketac silver. The microleakage was assessed using dye penetration test and stereomicroscope. The compressive and flexural strengths of these materials were measured using Instron Universal testing machine. The amount of fluoride released from the modified ionomers at pH 5 and pH 7 was estimated using Orion fluoride specific electrode. The obtained data was then subjected to statistical analysis. Results: Data was analysed using paired t-test for intergroup comparisons and unpaired t-test for intragroup comparisons. The overall microleakage (0.5±0.48) of zirconomer was significantly less (p=0.000) compared to ketac silver (1.9±0.83). Zirconomer demonstrated a significant higher compressive strength (330.25±60.14), flexural strength (33.058±2.36) than ketac silver (p= 0.000). Zirconomer demonstrated high fluoride release from day 1 to day 7 at both pH 5 and pH 7. Conclusion: Zirconomer demonstrated better physical and biological properties compared with ketac silver.